PSYCHOLOGICAL CAPITAL DAN KOMITMEN ORGANISASIONAL PENGARUHNYA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN PT. BPR MAJALENGKA JABAR - Sudirno, Dadang; Sri Mulyani, Hani; Prihartini, Endah (IKOPIN, 2021)
This study aims to determine the effect of Psychological Capital and Organizational Commitment on Organizational Citizenship Behavior among employees of PT. BPR Majalengka West Java. This study used a survey method with descriptive and verification approaches. The data collection technique used is by distributing questionnaires. The population in this study were employees of PT. BPR Majalengka West Java, with a sample of 55 respondents. The sampling technique used was saturated samples. The measurement scale of this study uses the Likert scale. Data analysis using classical assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing using partial test with t test. The results of research that have been conducted show that Psychological Capital, Organizational Commitment and Organizational Citizenship Behavior are in very high criteria. The results of the research are partially Psychological Capital has a significant effect on Organizational Citizenship Behavior and organizational commitment has a significant effect on Organizational Citizenship Behavior.